Producción de biogas mediante la digestión anaeróbica de los lodos flotantes de oxidación de aguas residuales de la ciudad de chepén - Corcio Burgos, Rossana Judith (2006)
The actual work explain that through the anaerobic digestion of floating muds of residual water lagoons of oxidation of the Chepen city is possible to produce biogas, using for that a bioreactor where are fitted out the ambiental factors which permit the development and activity of microorganisms. The productions of biogas is possible thanks to the elevated concentration of biogradable organics matter the floating muds count with, reflected in their organic content that: are digested by a group of bacteria as the methanogenics amony the principals. To get establish the anaerobias conditions, it was designed and constructed a bioreactor of 3 liters of capacity in which was set 1.5 Kilograms of floating mud to begin the process of digestion. This bioreactor was hermetically closed, equipped with a device of pression measurement and a system for gathering and storaging of biogas at 45 days of digestion it was achieved to produce 12.08 liters of biogas that was compressed in the bioreactor to a pression of 7.2 bars. Just as samples were extracted to determinate the concentration of methane. The average concentration was 84.01% methane (CH4) in produced biogas